Внутрішній монолог актора та пластика ляльки: взаємодія психологічного та фізичного в театральному мистецтві - Сільченко Тетяна; Silchenko Tetiana (Видавництво «Код», 2025)
Резюме. Метою статті є виявлення ролі внутрішнього монологу актора як джерела сценічної дії та аналіз його трансформації у фізичну виразність ляльки через психофізику виконавця. Дослідження зосереджене на взаємодії психологічного й тілесного у створенні сценічної присутності в театрі ляльок.

Abstract. The aim of the article is to reveal the role of the actor’s inner monologue as a source of stage action and to analyze its transformation into the puppet’s physical expressiveness through the psychophysics of the performer. The study focuses on the interaction of the psychological and the corporeal in creating stage presence in puppet theatre. The research methodology is based on an interdisciplinary approach that integrates theatre studies, acting, semiotics, and performance psychology. Its foundation lies in a qualitative analysis of the relationship between the actor’s inner monologue and the puppet’s plasticity as both a psychophysical and semiotic manifestation of stage action. The study employs: theoretical analysis of scholarly works on actor psychophysics and puppet theatre; phenomenological observation of the puppeteer’s stage experience; semiotic analysis of corporeality as a sign system; a psychophysical approach to studying the actor’s inner impulses; and empirical generalization of professional practice. This approach makes it possible to identify the mechanisms of animating an object on stage as a result of integrating the inner monologue with corporeal action. The research consists of a comprehensive analysis of the actor’s inner monologue as a source of psychophysical action in the conditions of puppet theatre, which operates through mediated corporeality. For the first time, the inner monologue is examined not only as a tool of inner speech but also as a structure-forming mechanism of stage presence, realized through rhythm, pause, silence, plastic gesture, and object action. The article proposes an interpretation of puppet plasticity as a semiotic extension of the actor’s inner action, opening a new perspective on theatrical expressiveness in the context of semiotics, corporeal communication, and psychophysics. The article also reveals the dual nature of the puppeteer as both the bearer of the character’s emotional logic and the manipulator of a physical object, which determines the unique character of stage transformation in puppet theatre.
Internal monologue of the actor and the puppet’s plasticity: interaction of the psychological and physical in theatrical art
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: внутрішній монолог; тілесність; театр ляльок; психофізика актора; пластика; ритм; сценічна присутність